2001
DOI: 10.1007/s005340100014
|View full text |Cite
|
Sign up to set email alerts
|

Solid and papillary tumor of the pancreas complicating agenesis of the dorsal pancreas

Abstract: We report the first documented case of a solid and papillary tumor of the pancreas (SPT) complicating agenesis of the dorsal pancreas. A 28-year-old female patient was referred to our hospital for a pancreatic tumor detected at a local hospital. The laboratory findings were all within normal limits. Diagnostic images revealed absence of the dorsal pancreas and the presence of a tumor located in the head of the pancreas. The tumor was solid, well demarcated, noncalcified, and hypovascular. Fine-needle aspiratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 9 publications
1
20
0
Order By: Relevance
“…Further judgment needs to be made by relying on the results of frozen section biopsy. Elements such as nuclear grade and mitotic rate, cellular pleomorphism, venous invasion, necrobiotic nests, and necrosis should be investigated as parameters of metastatic potential, although the malignant potential of SPT is very low [23]. Our cases of diagnosed SPT by the frozen section biopsy were only 44% (11/25).…”
Section: Surgical Strategies and Operative Methodsmentioning
confidence: 92%
“…Further judgment needs to be made by relying on the results of frozen section biopsy. Elements such as nuclear grade and mitotic rate, cellular pleomorphism, venous invasion, necrobiotic nests, and necrosis should be investigated as parameters of metastatic potential, although the malignant potential of SPT is very low [23]. Our cases of diagnosed SPT by the frozen section biopsy were only 44% (11/25).…”
Section: Surgical Strategies and Operative Methodsmentioning
confidence: 92%
“…[2][3] Congenital agenesis or hypoplasia of the dorsal pancreas is related to embryologic failure of the dorsal pancreatic bud, and is often associated with other anomalies, such as polysplenia syndrome. 4 Nakamura et al 5 reported a patient with a solid and papillary tumor complicating partial agenesis of the dorsal pancreas, in whom an accessory duct was detected by ERP. Strictly speaking, the absence of an accessory pancreatic duct is essential for a diagnosis of "true" absence of the dorsal pancreas.…”
Section: Discussionmentioning
confidence: 98%
“…SPT has been reported to occur occasionally in patients with pancreatic anormalies such as pancreatic dorsal agenesis [9,11] and pancreatic divicum [10,23]. There is another report of SPT in a young woman with Mulvihill-Smith syndrome (MSS), a congenital mental anomaly characterized by progeria-like aspect, multiple pigmented nevi, mental retardation, microcephaly, low stature and lack of facial subcutaneous fat [8].…”
Section: Discussionmentioning
confidence: 99%
“…But the cell origin of SPT and tumorigenesis are still enigmatic. Occasionally, SPT has been reported to be associated with extra- and pancreatic anomalies [8-11]. Here we present radiological, PET/CT and histological findings of a case of pancreatic SPT with concomitant urogenital malformations.…”
Section: Introductionmentioning
confidence: 86%